Village Fund Accountability: Does Village Chief’s Leadership Matter More Than Staff Competence? - Muhammad Taufiq (Innovation Business Management and Accounting Journal, 2024)
This study aims to investigate and compare the influence of leadership and competence on village fund accountability. While both factors are theoretically essential for sound financial governance, empirical evidence has shown inconsistent results regarding which variable acts as the primary driver for accountability. This research addresses the debate by evaluating whether the "tone at the top" set by the village Chief (leadership) holds more significance than the technical proficiency (competence) of the village officers. The research employs a qualitative approach through a Systematic Literature Review (SLR) and Qualitative Content Analysis. Data were synthesized from a selection of empirical studies published between 2019 and 2024. The analysis focused on comparing beta coefficients and significance levels across multiple research contexts to identify dominant patterns and anomalies, such as the "competence paradox," where technical skills occasionally yield negative correlations with accountability.The findings reveal that leadership is the more consistent and dominant predictor of village fund accountability. In studies where both variables were significant, the influence of leadership consistently outweighed that of staff competence. Notably, the study identifies that high competence without strong leadership oversight can lead to a decrease in accountability, suggesting that technical skills can be misapplied in the absence of an ethical institutional culture.The study concludes that the Chief of Village’s leadership indeed matters more than staff competence in securing fund integrity. While technical training for staff remains necessary, policy interventions should prioritize the cultivation of integrity-based leadership and robust internal control systems. This research contributes to the field of public sector management by highlighting that human capital must be governed by strong authoritative ethics to ensure the transparent management of public resources.